Adjuvant Use of Cyclosporine A in the Treatment of Primary Pterygium: A Systematic Review and Meta-Analysis. Issue 8 (August 2018) - Zhang, Qing; Bao, Ning; Liang, Kun; Tao, Liming
Abstract : Purpose: To evaluate the efficacy and tolerability of cyclosporine A (CsA) as an adjuvant treatment for primary pterygium. Methods: A comprehensive literature search from 7 databases (EMBASE, ISI Web of Science, PubMed, and the Cochrane Library for studies published in English and VIP, Wan Fang, and CNKI for studies published in Chinese). For the recurrence rate, pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using a random-effects model. Tolerability estimates were measured by OR for adverse events. Results: A total of 7 studies meeting the inclusion criteria were included in this meta-analysis. Compared with the group with adjunctive CsA usage, the control group (no adjuvant use of CsA) showed a significantly increased risk of pterygium recurrence (OR = 2.71; 95% CI, 1.62–4.54). No obvious heterogeneity was detected in the included studies. Subgroup analysis showed that adjuvant use of CsA with pterygium excision alone resulted in a significantly lower frequency of recurrence than was seen in the group without adjuvant use of CsA (OR = 3.16; 95% CI, 1.18–8.84). However, there is no significant difference in pterygium recurrence between the subgroup (CsA + pterygium excision + limbal conjunctival autograft or flap rotation) and the subgroup without adjunctive CsA usage (pterygium excision + limbal conjunctival autograft or flap rotation). Conclusions: This meta-analysis suggests that adjuvant use of CsA can significantly reduce the risk of pterygium recurrence compared with pterygium excision alone, whereas adjuvant use of CsA may not reduce the risk of pterygium recurrence in terms of pterygium excision + limbal conjunctival autograft or conjunctival flap rotation.